Maternal and Neonatal Outcomes by Mode of Delivery in Obese Women With a Previous Cesarean Section [5R]. (May 2017) - Coviello, Elizabeth; Clark-Ganheart, Cecily A.; Huang, Chun-Chih; Landy, Helain; Iqbal, Sara; Reddy, Uma
Abstract : INTRODUCTION: To compare maternal and neonatal outcomes for obese women with a prior cesarean delivery by attempted mode of delivery. METHODS: In the Consortium on Safe Labor, 4, 840 singleton deliveries greater or equal to 37 weeks with a prior cesarean delivery and eligible for vaginal delivery were classified by body mass index (BMI) class I, II, III. Maternal and neonatal outcomes between planned repeat cesarean delivery (rCD, n=2, 364) and trial of labor after cesarean delivery (TOLAC, n=2, 506) were compared using chi-square. Maternal outcomes included postpartum deep vein thrombosis/pulmonary embolism (DVT/PE), postpartum hemorrhage (PPH), maternal ICU admission and chorioamnionitis. Multivariable logistic regression was used to calculate adjusted OR (aOR), adjusting for maternal age, race, insurance status, hypertensive disorders, diabetes mellitus, and obesity class. RESULTS: TOLAC was attempted by 51.5% of women. Less women attempted VBAC with increasing obesity class, 54.8%, 50.7%, 45.4%. The VBAC success rate decreased with increasing class of obesity, 58.7%, 53.5%, 40.6%. There was an increased likelihood of chorioamnionitis and postpartum DVT/PE with TOLAC compared to rCD (aOR 5.72; 95% CI 3.22-10.15 and aOR 3.03; 95% CI 1.18-7.76), respectively. Women with successful VBAC were 6.95 times more likely to have a DVT/PE compared to failed TOLAC with rCD after adjusting for confounders (95% CI 1.56-30.92). There was no association between mode of delivery and PPH, maternal ICU admission or neonatal outcomes. CONCLUSION: Among obese women with a prior cesarean delivery, increasing BMI was associated with lower TOLAC attempts and success rates. Postpartum DVT/PE and chorioamnionitis occurred more frequently in those undergoing TOLAC.